2017
DOI: 10.26789/aeb.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Potential correlated environmental factors leading to the niche seg- regation of ammonia-oxidizing archaea and ammonia-oxidizing bac- teria: A review

Abstract: Ammonia oxidation is an important step of the nitrogen cycle and was considered to be conducted only by ammonia-oxidizing bacteria (AOB) for a long time. The discovery of ammonia-oxidizing archaea (AOA) caused consideration of the relative contributions of these two functional groups in different niches and factors resulting in their niche segregation. Previous studies showed that some environmental factors may correlate to the abundance and distribution of AOA and AOB, including ammonia/ammonium concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…1B and S7B); this might be associated with the prevalence of archaea in extreme environments (Cavicchioli, 2006) and their functional diversification (e.g., ammonia oxidation, methane metabolism and organic matter degradation) (Orphan et al ., 2002; Könneke et al ., 2005; Lloyd et al ., 2013). Moreover, compared with AOB, AOA have a higher affinity for the substrate and oxygen; therefore, the latter group could survive under oligotrophic conditions during the biogeochemical cycles of carbon and nitrogen (Liu et al ., 2017). We also revealed that the associations were stronger between kingdoms than within a kingdom for archaeal taxa in the Tibetan alpine grasslands (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1B and S7B); this might be associated with the prevalence of archaea in extreme environments (Cavicchioli, 2006) and their functional diversification (e.g., ammonia oxidation, methane metabolism and organic matter degradation) (Orphan et al ., 2002; Könneke et al ., 2005; Lloyd et al ., 2013). Moreover, compared with AOB, AOA have a higher affinity for the substrate and oxygen; therefore, the latter group could survive under oligotrophic conditions during the biogeochemical cycles of carbon and nitrogen (Liu et al ., 2017). We also revealed that the associations were stronger between kingdoms than within a kingdom for archaeal taxa in the Tibetan alpine grasslands (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Alpine grassland ecosystems have two dominant vegetation types: alpine steppes (characterized by low MAP, oligotrophic conditions and high soil pH), and alpine meadows (characterized by high MAP, copiotrophic conditions and low soil pH; Zhang, 1988). Bacterial and archaeal communities in N‐ and P‐limited alpine grasslands are dominated by oligotrophic clades, such as Actinobacteria , Acidobacteria and AOA (Fierer et al ., 2007; Yang et al ., 2008; Liu et al ., 2017; Ma et al ., 2019). Therefore, soil bacteria and archaea have stronger connections in alpine steppes with oligotrophic conditions and high soil pH.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Thaumarchaeota as a dominant archaeal phylum might be explained by three main factors. First, compared with ammonia-oxidizing bacteria, ammonia-oxidizing archaea have a higher affinity for substrate and oxygen; therefore, the latter group could survive under oligotrophic conditions during the biogeochemical cycles of carbon and nitrogen [38]. Second, unlike ammonia-oxidizing bacteria, ammonia-oxidizing archaea assimilate CO 2 via an energy-saving method (the 3-hydroxypropionate/4hydroxybutryrate pathway) for autotrophic growth, and thereby use organic carbon sources directly [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The maps showed that soil bacterial and archaeal taxa in the alpine steppe (high soil pH) had closer relationships than in the alpine meadow (low soil pH). One plausible explanation for this observation is that the bacterial and archaeal communities in N-and P-limited alpine grasslands [55,56] are dominated by oligotrophic clades such as Actinobacteria, Acidobacteria, and ammonia-oxidizing archaea [38,57]. Therefore, soil bacterial and archaea have stronger connections in the alpine steppe (oligotrophic conditions and high soil pH) to resist pressure caused by an energy deficit [30].…”
Section: Discussionmentioning
confidence: 99%
“…Further examination of the published articles in this journal indicated that the topics of interest to readers the most by this journal are on enzymes, the protein structure of the metal center of a dehalogenase hydrolyzing chlorothalonil (Chen et al, 2010) and a low-temperature endo-β-1,4-mannase from Bacillus subtilis TD7 with expression in E. coli (Li et al, 2018); the evolutionary relationship between ammoniaoxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) (Liu et al, 2017); and the current plastic issue to our society (Gu, 2017). The immediate following these with the highest attention include inhibition of sulfate-reducing activity in oilfield (Liu et al, 2016) and bioleaching (Maulani et al, 2016).…”
mentioning
confidence: 99%